Repair of cisplatin-induced DNA interstrand crosslinks by a replication-independent pathway involving transcription-coupled repair and translesion synthesis - Enoiu, Milica (Oxford University Press, 2012)
DNA interstrand crosslinks (ICLs) formed by antitumor agents, such as cisplatin or mitomycin C, are highly cytotoxic DNA lesions. Their repair is believed to be triggered primarily by the stalling of replication forks at ICLs in S-phase. There is, however, increasing evidence that ICL repair can also occur independently of replication. Using a reporter assay, we describe a pathway for the repair of cisplatin ICLs that depends on transcription-coupled nucleotide excision repair protein CSB, the general nucleotide excision repair factors XPA, XPF and XPG, but not the global genome nucleotide excision repair factor XPC. In this pathway, Rev1 and Polζ are involved in the error-free bypass of cisplatin ICLs. The requirement for CSB, Rev1 or Polζ is specific for the repair of ICLs, as the repair of cisplatin intrastrand crosslinks does not require these genes under identical conditions. We directly show that this pathway contributes to the removal of ICLs outside of S-phase. Finally, our studies reveal that defects in replication- and transcription-dependent pathways are additive in terms of cellular sensitivity to treatment with cisplatin or mitomycin C. We conclude that transcription- and replication-dependent pathways contribute to cellular survival following treatment with crosslinking agents.